Legal Study of Plastic Waste Handling for Street food Business Actors - Abim Dwi Nugroho; Dianita Utami; Zahran Muhammad Ikhwan; Endang Sutrisno; Harmono Harmono (Jurnal Impresi Indonesia, 2024)
In Cirebon City, plastic waste is still an unresolved problem. With the increase in population, there will be an increase in the volume of waste generated by human activities. This study aims to determine the procedures for handling plastic waste and the elements that influence the management of plastic waste in the city of Cirebon. The type of research used is empirical juridical research using qualitative data, initial research by examining secondary data, then continued with research in the field or community. Research data obtained through field observations or obtained through interviews. This research looks at written legal products such as Law Number 18 of 2008 concerning Waste Management, and Cirebon City Regional Regulation Number 4 of 2018 concerning Waste Management. Research on this issue is carried out descriptively analytically, explaining how written law can prevent environmental pollution. Waste management is difficult to resolve due to lack of awareness among business actors and insufficient socialization and efforts from the government. Law No. 18/2008 contains administrative provisions, civil liability, several rights to sue, and criminal sanctions. Regarding administrative sanctions, the above regulation authorizes the regent/mayor to impose administrative sanctions on waste managers who violate the provisions stipulated in the permit. The sanctions given are in the form of government coercion, forced money, and license revocation.